SOURCING AND SUSTAINING INVESTMENT FINANCE IN LOCAL GOVERNMENT MASS TRANSIT OPERATIONS IN NIGERIA: A STUDY IN SUSTAINABLE DEVELOPMENT - EZE, Eze Anoke; BIEREENU-NNABUGWU, Makodi (Socialscientia: Journal of Social Sciences and Humanities, 2021)
This study interrogates the subject of sourcing and sustaining effective investment finance for sustainable local government mass transit operations in Nigeria. From a prism of a segmented and underserved market that is neglected despite its economic and demographic potentials, the study underlines the place of clearly defined sources of finance and sustainable financial investment in effective mass transit operations in the Nigerian Local Government system. Using the analytical method of social research, the study explores the financial status, source options and models for sustainable investment in local government mass transit operations in Nigeria. Secondary data and other information were gathered and analysed procedurally through the identification of themes, patterns and alternative explanations. Despite the manifold forces militating against successful mass transit operations, it was found that a properly structured programme, based on the private-public partnership model and anchored on the buy in of institutional stakeholders, has the potential to provide local government mass transit services on a sustainable basis.